Analisis Perilaku Produksi Kelapa Sawit di Provinsi Sumatera Selatan Analysis Of Oil Palm Production Behavior In The Province Of South Sumatera - Aisyah (Universitas Bojonegoro, 2024)
The objectives of this study were: (1) To analyze the influence of the development of production and land productivity on oil palm plants in the province of South Sumatra. (2) To analyze the factors that affect the area of oil palm land in South Sumatra province. and (3) To analyze the factors that influence oil palm production in the province of South Sumatra. This research will be conducted in January to February 2021. The method used in this research is historical method of data sources or secondary data. The data used in this study are secondary data, which is taken from 2005 to 2019. Data was collected from various agencies. such as the Central Statistics Agency, the South Sumatra Plantation Service and other agencies. It is suspected that the factors that indicate the development of oil palm production are the area of oil palm plantations and the productivity of oil palm lands.The results of this study are the development of productivity, area, and production of oil palm plantations in South Sumatra Province from 2005 to 2019 which has increased every year with growth rates of 2.3%, 4.71%, and 7,11% by year although it tends to fluctuate. The productivity of oil palm in South Sumatra is determined by the area and production of oil palm in South Sumatra. The area of oil palm plantations in the province of South Sumatra is significantly influenced by the production factor of the price of rubber and the production factor of the minimum wage for labor in South Sumatra. The production of oil palm plantations in the province of South Sumatra is significantly influenced by the production factor for the area of oil palm plantations and the minimum wage for labor in South Sumatra Province.